PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP OPINI GOING CONCERN - Julian Maradina (Universitas Pamulang, 2019)
The following research discusses analysis and discusses company financial planning in ongoing audit opinion. In the following research the method used is quantitative. The testing of the hypothesis in the research and the method used is logistic regression analysis using the version 22.0 Statistical Package for the Social Sciences (SPSS) program. The following research uses a purposive sampling technique, producing 26 (twenty six) manufacturing companies for 3 years so that the total sample is 78. The results of the study, liquidity which is proxied by the current ratio does not affect Going Concern Audit Opinion. The profitability of the return on asset (ROA) proxy has no effect on the going-concern audit opinion. Solvency of the debt proxy to total assets (DTA) has an influence on the going-concern audit opinion.